Hippocampal vascularization patterns exert local and distant effects on brain structure but not vascular pathology in old age. Issue 3 (4th June 2021) - Vockert, Niklas; Perosa, Valentina; Ziegler, Gabriel; Schreiber, Frank; Priester, Anastasia; Spallazzi, Marco; Garcia-Garcia, Berta; Aruci, Merita; Mattern, Hendrik; Haghikia, Aiden; Düzel, Emrah; Schreiber, Stefanie; et al.
Abstract: The hippocampus within the medial temporal lobe is highly vulnerable to age-related pathology such as vascular disease. We examined hippocampal vascularization patterns by harnessing the ultra-high resolution of 7 Tesla magnetic resonance angiography. Dual-supply hemispheres with a contribution of the anterior choroidal artery to hippocampal blood supply were distinguished from single-supply ones with a sole dependence on the posterior cerebral artery. A recent study indicated that a dual vascular supply is related to preserved cognition and structural hippocampal integrity in old age and vascular disease. Here, we examined the regional specificity of these structural benefits at the level of medial temporal lobe sub-regions and hemispheres. In a cross-sectional study with an older cohort of 17 patients with cerebral small vessel disease (70.7 ± 9.0 years, 35.5% female) and 27 controls (71.1 ± 8.2 years, 44.4% female), we demonstrate that differences in grey matter volumes related to the hippocampal vascularization pattern were specifically observed in the anterior hippocampus and entorhinal cortex. These regions were especially bigger in dual-supply hemispheres, but also seemed to benefit from a contralateral dual supply. We further show that total grey matter volumes were greater in people with at least one dual-supply hemisphere, indicating that the hippocampal vascularization pattern has more far-reaching structural implications beyond the medial temporal lobe. A mediation analysis identified total grey matter as a mediator of differences in global cognition. However, our analyses on multiple neuroimaging markers for cerebral small vessel disease did not reveal any evidence that an augmented hippocampal vascularization conveys resistance nor resilience against vascular pathology. We propose that an augmented hippocampal vascularization might contribute to maintaining structural integrity in the brain and preserving cognition despite age-related degeneration. As such, the binary hippocampal vascularization pattern could have major implications for brain structure and function in ageing and dementia independent of vascular pathology, while presenting a simple framework with potential applicability to the clinical setting. Abstract : Vockert et al. report that an augmented hippocampal vascular supply provides brain structural benefits at multiple levels, including medial temporal lobe substructure volumes and total grey matter volume, leading to improved cognition. Thus, the hippocampal vascular pattern could have major implications for ageing and dementia. Graphical Abstract: